2020
DOI: 10.31235/osf.io/ve4z7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning Loss Due to School Closures During the COVID-19 Pandemic

Abstract: Suspension of face-to-face instruction in schools during the COVID-19 pandemic has led to concerns about consequences for student learning. So far, data to study this question have been limited. Here we evaluate the effect of school closures on primary school performance using exceptionally rich data from the Netherlands (n≈350,000). The Netherlands represents a best-case scenario with a relatively short lockdown (8 weeks) and a high degree of technological preparedness. We use the fact that national exams too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
376
6
35

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 326 publications
(431 citation statements)
references
References 0 publications
14
376
6
35
Order By: Relevance
“…The shutdown of schools in 2020 due to the COVID-19 pandemic required students to be educated from home which has been linked to lower performance on national tests [3], higher stress and anxiety [7,9], lower sleep quality [8], as well as a general decrease in student's wellbeing [5,6,13]. In this study, we examined the impact of the school closures on the performance of K12 students in an online learning environment for mathematics-building on a large dataset compromising over 30,000 K-12 students and over 800,000 computed problem sets-by contrasting students' performance before the shutdown against their performance during the shutdown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The shutdown of schools in 2020 due to the COVID-19 pandemic required students to be educated from home which has been linked to lower performance on national tests [3], higher stress and anxiety [7,9], lower sleep quality [8], as well as a general decrease in student's wellbeing [5,6,13]. In this study, we examined the impact of the school closures on the performance of K12 students in an online learning environment for mathematics-building on a large dataset compromising over 30,000 K-12 students and over 800,000 computed problem sets-by contrasting students' performance before the shutdown against their performance during the shutdown.…”
Section: Discussionmentioning
confidence: 99%
“…An important consequence of school shutdowns concerns a widening of the education gap, i.e. the difference in academic performance between students from different subgroups, such as low-income and high-income students [3,4]. A recent study from the UK found that children from low-income families are less likely to participate in online classes, are spending 30% less time learning at home, and have limited access to educational resources [10].…”
Section: Effects Of School Closures On Performance In Mathematicsmentioning
confidence: 99%
See 3 more Smart Citations